2006
DOI: 10.4314/gmj.v39i1.35978
|View full text |Cite
|
Sign up to set email alerts
|

Squamous cell carcinoma of the mastoid – a report of two cases

Abstract: SUMMARYMalignant tumours of the mastoid are rare, the majority being squamous cell carcinomas. We report two cases whose clinical presentation mimicked mastoid abscess with intracranial complications. The first case is a twenty year Nigerian lady who presented to the Emergency Room of the Otorhinolaryngology Department with a one month history of headache, low grade fever, left facial palsy, neck stiffness and left post-auricular swelling on a background of left chronic suppurative otitis media since childhood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 8 publications
1
10
0
Order By: Relevance
“…1 Lasissi et al reported a case of recurrent left ear discharge, which worsened six months before presentation. 5 Though the history is quite close to our case the associated symptoms severe deep-seated left otalgia, left hemi-cranial headache, hearing loss, vertigo, and tinnitus, facial nerve palsy was absent in our case. Hu X-D reported a case with bloody discharge, painless skin ulceration in the mastoid area, where peripheral facial paralysis was seen, 1 but in our patient, we only had an ulcerated mastoid region with mastoid fistula.…”
Section: Discussionsupporting
confidence: 72%
“…1 Lasissi et al reported a case of recurrent left ear discharge, which worsened six months before presentation. 5 Though the history is quite close to our case the associated symptoms severe deep-seated left otalgia, left hemi-cranial headache, hearing loss, vertigo, and tinnitus, facial nerve palsy was absent in our case. Hu X-D reported a case with bloody discharge, painless skin ulceration in the mastoid area, where peripheral facial paralysis was seen, 1 but in our patient, we only had an ulcerated mastoid region with mastoid fistula.…”
Section: Discussionsupporting
confidence: 72%
“…Middle ear carcinoma in a patient as young as 18 years has been reported by Deka RC whereas O.A Lasisi has reported a similar case in a 20 year old female. 4,5 Chronic otorrhoea, as seen in COM may be a major etiological factor. Presence of long standing COM with a recent change in the pattern of symptoms like obstinate otalgia is a pointer towards the unlikely disease.…”
Section: Discussionmentioning
confidence: 99%
“…The first case in Africa was reported in 2005 which highlights the dilemma of diagnosis because of background of CSOM in which it arises. 7 The patient presented with discharge and heaviness in left ear accompanied by discharge and swelling in postaural area. Initially, the diagnosis of CSOM atticoantral type with polyp, complicated by mastoid (zygomatic) abscess was made and incision and drainage was done.…”
Section: Discussionmentioning
confidence: 99%